2015
DOI: 10.1155/2015/368124
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-Supported Hip Implants: Short Term Clinical Results

Abstract: We developed a new povidone iodine coating technology for titanium hip implants and performed a clinical trial to assess its usefulness in suppressing postoperative infection. Results indicate that iodine-supported titanium has favorable antibacterial activity, biocompatibility, and no cytotoxicity. Thirty joints in 28 patients were treated using iodine-supported implants. Fourteen joints were revision total hip arthroplasty (THA) after periprosthetic infection, 13 were primary THA for immunosuppressive condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…An innovative technology using iodine to produce porous anodic oxide implant surfaces with the antiseptic properties of iodine was studied in a prospective uncontrolled cohort study for both prophylaxis in high risk patients, and for treatment in confirmed MSK infection cases . Confirmatory reports on subsets of these patients with hip replacement implants or fixator pins reported no hip implant infections and decreased pin tract infections respectively …”
Section: Resultsmentioning
confidence: 99%
“…An innovative technology using iodine to produce porous anodic oxide implant surfaces with the antiseptic properties of iodine was studied in a prospective uncontrolled cohort study for both prophylaxis in high risk patients, and for treatment in confirmed MSK infection cases . Confirmatory reports on subsets of these patients with hip replacement implants or fixator pins reported no hip implant infections and decreased pin tract infections respectively …”
Section: Resultsmentioning
confidence: 99%
“…Two more recent non-comparative studies – one investigating iodine coating and megaprosthesis, 54 the other investigating total hip arthroplasty (THA) 55 – confirmed the safety and efficacy of the technology at longer follow-ups. Based on these findings, clinical trials are currently ongoing to meet the regulatory requirements for market approval.…”
Section: Antibacterial Coating In Orthopaedics and Traumamentioning
confidence: 95%
“…Two more recent non-comparative studies -one investigating iodine coating and megaprosthesis [45], the other investigating total hip arthroplasty (THA) [46] -confirmed the safety and efficacy of the technology at longer follow-ups. Based on these findings, clinical trials are currently ongoing to meet the regulatory requirements for market approval (Fig.…”
Section: Iodine Coatingmentioning
confidence: 95%